Cost‐effectiveness of second‐line empagliflozin versus liraglutide for type 2 diabetes in the United States. Issue 4 (11th January 2022) - Reifsnider, Odette S.; Pimple, Pratik; Brand, Sarah; Bergrath Washington, Evelien; Shetty, Sharash; Desai, Nihar R.
Abstract: Aim: To estimate the cost‐effectiveness of sequential use of the sodium‐glucose co‐transporter‐2 inhibitor empagliflozin and glucagon‐like peptide‐1 receptor agonist liraglutide after metformin in patients with type 2 diabetes (T2D) from the US payer perspective. Materials and Methods: An economic simulation model with a lifetime horizon was developed to estimate T2D‐related complications (including cardiovascular [CV] death, myocardial infarction, stroke, and renal outcomes) using EMPA‐REG OUTCOME data or UK Prospective Diabetes Study risk equations, in patients with or without a history of cardiovascular disease (CVD), respectively. Evidence synthesis methods were used to provide effectiveness inputs for empagliflozin and liraglutide. Population characteristics, adverse event rates, treatment escalation, costs ($2019), and utilities (both discounted 3%/year) were taken from US sources. Results: Compared with second‐line liraglutide in the overall T2D population, second‐line empagliflozin was dominant as it was associated with lower total lifetime cost ($11 244/patient less) and resulted in a quality‐adjusted life‐year (QALY) gain (0.32/patient). Second‐line empagliflozin was associated with reductions in CV death (by 5%) and lower cumulative complication rates in patients with CVD (by 2%), relative to second‐line liraglutide. These findings were consistent among patients with co‐morbid CVD, with gains in incremental QALYs (0.43/patient) and lower lifetime cost (by $10 175/patient) relative to second‐line liraglutide. Scenario analyses consistently showed dominance for second‐line empagliflozin. Conclusion: For patients with T2D, use of second‐line empagliflozin combined with metformin was a dominant strategy for US payers, associated with extended survival, improved QALYs, and lower costs compared with second‐line liraglutide.